Pengaruh Lingkungan Kerja Dan Pemberdayaan Karyawan Terhadap Kinerja Karyawan Pada Universitas Nusa Nipa - Sujila, Kristina; Wisang, Imelda Virgulia; Bure, Maria Rasdiana (Universitas Nusa Nipa Maumere, 2025)
This study aims to: (1) identify the description of Employee Performance, Work Environment, and Employee Empowerment; (2) analyze the effect of Work Environment and Employee Empowerment on Employee Performance, both partially and simultaneously.The population in this study consists of 78 employees of Nusa Nipa University. Since the population is limited, the research was conducted using a census or saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was carried out using the F-test and t-test. The results of the descriptive analysis show that the Employee Performance variable falls into the “good” category, the Work Environment variable is in the “fairly good” category, and the Employee Empowerment variable is in the “good” category. The results of the t-test indicate that partially, the Work Environment variable has a positive and significant effect on Employee Performance. Likewise, the Employee Empowerment variable has a positive and significant effect on Employee Performance. The results of the F-test show that simultaneously, the Work Environment and Employee Empowerment variables have a significant effect on Employee Performance. The determination analysis results show that both independent variables in this study are able to explain 46.8% of the variation in Employee Performance at Nusa Nipa University.